POTENSI DAN MASA DEPAN SERAT ALAM INDONESIA SEBAGAI BAHAN BAKU ANEKA INDUSTRI - Ono Suparno (Jurnal Teknologi Industri Pertanian, 2020)
Indonesia is one of the producing countries of natural fibre commodities, both vegetable and animal fibres. Indonesia exports natural fibres and at the same time needs a large quantity of natural fibers which is satisfied by imports. The natural fibre user industry contributes as a source of the state revenue. This article was written descriptively through a literature review and an analysis of data on the potential and future of Indonesian natural fibres as raw materials for various industries. The results of this study indicated that natural fibre from Indonesia had the potential to be used as raw materials for various industries by increasing the quantity of supplies and their qualities; the uses of natural fibres are not only for conventional uses, but continues to grow with the development of science, technology and art to create innovations based on natural fibres and take awareness of the importance of environmentally friendly products; and natural fibres have good prospects or technoeconomically feasibile to be developed as raw materials for various industries. Keywords: business feasibility, export, fibre uses, industry, natural fibre, production, raw material